Analysis of a Tiltrotor Vertical Take-off and Landing Unmanned Aerial Vehicle: CFD Approach. Issue 1 (April 2021) - Sharma, Shailesh; Sharma, Rajkumar; Kumar, Veneet; Chandel, Siddharth
Abstract: In this current era of technology VTOL UAVS is an emerging technology that is becoming popular for its variety of applications like Agriculture, Civil, and military for Surveillance, rescue missions, and patrolling. These types of aircraft came into existence as the solution to many issues like lack of runways in rural areas and dense forests. VTOL UAV is a hybrid of a helicopter and fixed-wing aircraft because it has the functionality of both types of aircraft. These aircraft possess high hovering efficiencies like a helicopter and a better cruising speed like a fixed-wing aircraft with an enhanced payload capacity. Many interesting applications of these aircraft is attracting researchers to work in this field. In this paper, a CFD approach has been adopted for the analysis of TURAC tilt-rotor type VTOL UAV with the help of XFLR software.